2007
DOI: 10.1089/dia.2006.0014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Patient Education Booklet (SimpleStart) Effect on Postprandial Glucose Control in Type 2 Diabetes

Abstract: An educational program incorporating Simple Start facilitates patient behavioral changes, decreasing post-meal hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 8 publications
0
15
0
3
Order By: Relevance
“…A number of randomised trials in different clinical settings and populations have reported that the provision of audio-visual information in addition to that provided in a standard consultation enhances patient knowledge and understanding [9-12]. King and colleagues [9] evaluated an educational DVD and booklet in addition to the information provided in a standard consultation on the degree of post-prandial glucose control among individuals with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of randomised trials in different clinical settings and populations have reported that the provision of audio-visual information in addition to that provided in a standard consultation enhances patient knowledge and understanding [9-12]. King and colleagues [9] evaluated an educational DVD and booklet in addition to the information provided in a standard consultation on the degree of post-prandial glucose control among individuals with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…King and colleagues [9] evaluated an educational DVD and booklet in addition to the information provided in a standard consultation on the degree of post-prandial glucose control among individuals with type 2 diabetes. In this study, provision of additional audio-visual information was associated with a significant increase in reported self-monitoring of blood glucose concentrations, a reduction in post-prandial hyperglycaemia, and a lower mean blood glucose concentration, when compared with standard care [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 There are few published studies on written information given to people with diabetes, particularly in primary care. Those that do exist refer to improvement in HbA 1c levels, [34][35][36][37] postprandial glycemia 38 and adherence to treatment. 39 We thus carried out this study to evaluate the effectiveness of the information given to the person with diabetes by means of leaflets and compare the results with those of a control group that only received the usual advice given during medical visits.…”
mentioning
confidence: 99%
“…39 Several randomized studies have evaluated the use of educational material presented via a DVD or video format to enhance knowledge and treatment compliance, in a range of clinical settings. [40][41][42][43] The conclusion of each of these evaluations was that the addition of the DVD or video improved treatment compliance and was an effective method of delivering health care information. [40][41][42][43] To evaluate whether a DVD may be an effective adjunct tool to delivering dietary and weight management information for women during pregnancy, we conducted and have reported the findings of our nested randomized trial.…”
Section: Strategies To Improve Knowledge In a Time Poor Environmentmentioning
confidence: 99%